Trace metals (Cu, Zn, Cd and Pb) in juvenile fish from estuarine nurseries along the Portuguese coast - Vasconcelos, Rita P.; Reis-Santos, Patrick; Maia, Anabela; Ruano, Miguel; Costa, Maria J.; Cabral, Henrique N. (Scientia Marina, 2011)
Organic and inorganic pollution can impact organisms directly and affect condition, growth and survival of juvenile fish which use estuaries as nurseries, and thereby affect marine adult populations quantitatively and qualitatively. Trace element contamination (Cu, Zn, Cd, Pb) in juveniles of commercial fish Solea solea, Solea senegalensis, Platichthys flesus, Diplodus vulgaris and Dicentrarchus labrax collected in putative nurseries of the main Portuguese estuaries (with diverse intensities and sources of anthropogenic pressures) was determined via atomic absorption spectrometry. Contamination was significantly different among species. Similar levels of contamination were found among estuaries, except for D. vulgaris. Cu and Zn concentrations ranged from 1.0 to 2.1 and 14 to 59 μg g-1 muscle dry weight respectively; while Cd and Pb concentrations were very low. The results indicate that juvenile migration to off-shore habitats is associated with low export of contamination, and no particular estuary increases the potential contamination of adult stocks. This knowledge is of the utmost importance in view of the ecological and economical value of these species and their use of estuarine areas as nurseries.